Purimeth: an integrated web-based tool for estimating and accounting for tumor purity in cancer DNA methylation studies - Nana Wei (AIMS Press, 2021)
Proportion of cancerous cells in a tumor sample, known as "tumor purity", is a major source of confounding factor in cancer data analyses. Lots of computational methods are available for estimating tumor purity from different types of genomics data or based on different platforms, which makes it difficult to compare and integrate the estimated results. To rectify the deviation caused by tumor purity effect, a number of methods for downstream data analysis have been developed, including tumor sample clustering, association study and differential methylation between tumor samples. However, using these computational tools remains a daunting task for many researchers since they require non-trivial computational skills. To this end, we present Purimeth, an integrated web-based tool for estimating and accounting for tumor purity in cancer DNA methylation studies. Purimeth implements three state-of-the-art methods for tumor purity estimation from DNA methylation array data: InfiniumPurify, MEpurity and PAMES. It also provides graphical interface for various analyses including differential methylation (DM), sample clustering, and purification of tumor methylomes, all with the consideration of tumor purities. In addition, Purimeth catalogs estimated tumor purities for TCGA samples from nine methods for users to visualize and explore. In conclusion, Purimeth provides an easy-operated way for researchers to explore tumor purity and implement cancer methylation data analysis. It is developed using Shiny (Version 1.6.0) and freely available at http://purimeth.comp-epi.com/.